The staging performance of a modified tumor-node-metastasis staging system incorporated with lymphovascular invasion in patients with esophageal squamous cell carcinoma - Zhuang, Weitao; Wu, Hansheng; Chen, Rixin; Ben, Xiaosong; Huang, Shujie; Zhou, Zihao; Wu, Junhan; Tang, Yong; Qiao, Guibin (Frontiers in Oncology, 2022)
Background. Lymphovascular invasion (LVI) is recognized as an unfavorable prognostic factor for many solid tumors. However, its staging value has not been adequately illustrated in esophageal squamous cell carcinoma (ESCC). Methods. The clinicopathologic relevance and prognostic impact of LVI were retrospectively analyzed in 822 patients with surgically treated ESCC. Univariate and multivariate analyses were used to determine the independent prognostic factors. Subgroup analyses stratified by pathological stages, nodal status and invasive depth were conducted using Kaplan–Meier method and log-rank test. Multiple staging models based on overall survival (OS) were constructed using Cox regression and evaluated by Harrell's concordance index (C-index), integrated discrimination improvement (IDI), and net reclassification index (NRI). Results. LVI was detected in 24.6% of ESCC patients, and its prevalence increased with a higher pathological stage (p < 0.001). In multivariate analysis, LVI was found to be an independent prognostic factor for OS [Hazard ratio (HR) = 1.545, 95% CI, 1.201–1.986), and was associated with unfavorable outcomes in stage I to III ESCC, regardless of nodal status and invasive depth. The staging model that incorporated LVI as an independent factor achieved the greatest improvement in accuracy (ΔC-index: 2.9%), and the greatest added value (IDI 2.8%, p < 0.01; NRI 13.7%, p < 0.05) for prediction of OS in ESCC patients. Conclusions. LVI can facilitate further survival stratification in ESCC patients. The adoption of LVI as an independent staging factor in the current cancer staging system should be considered and further validated.